1995
DOI: 10.2172/125043
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy and EPR studies of oriented spinach thylakoid preparations

Abstract: In this study, oriented Photosystem 11 (PS n) particles from spinach chloroplasts are studied with electron paramagnetic resonance (EPR) and x-ray absorption spectroscopy VAS) to determine more details of the structure of the oxygen evolving complex (OEC).The nature of halide binding to Mn is also studied with C1 K-edge and Mn EXAFS (extended x-ray absorption fine structure) of Mn-C1 model compounds, and with Mn EXAFS of oriented PS 1T in which Br has replaced C1.In chapter 2, oriented PS 11 particles from spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 76 publications
(120 reference statements)
1
4
0
Order By: Relevance
“…For simplicity the dichroic ratio of the ∼3260 G feature of the tyrosine Y D ox (signal II "slow") EPR spectra (24,70) at two extreme angles (0°and 90°) between the sample face and the applied magnetic field (for details see Figure S3) is used to determine the mosaic spread. This method is based on the previous finding that this ratio is inversely related (72) to the mosaic spread as measured from the angle dependence of the cyt b 559 EPR spectra, following the protocol of Blum et al (69). In addition, we confirmed that with the slightly different method of Dau et al (58) the numbers are practically identical (difference ∼5% in the determination of the coordination numbers).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…For simplicity the dichroic ratio of the ∼3260 G feature of the tyrosine Y D ox (signal II "slow") EPR spectra (24,70) at two extreme angles (0°and 90°) between the sample face and the applied magnetic field (for details see Figure S3) is used to determine the mosaic spread. This method is based on the previous finding that this ratio is inversely related (72) to the mosaic spread as measured from the angle dependence of the cyt b 559 EPR spectra, following the protocol of Blum et al (69). In addition, we confirmed that with the slightly different method of Dau et al (58) the numbers are practically identical (difference ∼5% in the determination of the coordination numbers).…”
Section: Resultssupporting
confidence: 77%
“…However, it is cumbersome to collect EPR spectra of cyt b 559 in several orientations from each sample. We devised a simpler method of correlating the dichroism in the EPR signal from the tyrosine Y D ox (24,70,71), which is much easier to collect, to that determined from cyt b 559 (31,58,69,72). X-band (9.2 GHz) EPR spectra of the signal II region (near g = 2.00) were taken for layered samples oriented 0° and 90° in the magnetic field at 20 K and 50 µW power with 2.5 G modulation amplitude.…”
Section: Mosaic Spread Determination By Eprmentioning
confidence: 99%
See 1 more Smart Citation
“…The dichroic ratio of the oriented samples used for XAS experiments ranged from 3.3 to 5.3 with an average of 3.9 ± 0.6. According to the calibration curve of Andrews, 56 which relates the dichroic ratio to Ω via the angular dependence of the cytochrome b 559 EPR signal, the mosaic spread was found to be 15–20°. For evaluation of the angle dependence of the apparent coordination numbers N app, j , derived from polarized EXAFS data (sections 2.5 and 3.5), 30 the lower limit of 20° was chosen.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature was 8 K, the microwave power 0.5 mW and the modulation amplitude 32 G. None of the batches of Ca 2+ -depleted and Ca 2+ -reconstituted samples contained detectable amounts of Mn II . In order to determine the mosaic spread Ω as a measure for the degree of disorder (Section S2 of the Supporting Information), EPR spectra of Y D • (D2-Tyr160) at g = 2 were collected from one-dimensionally ordered samples at orientations of 0° and 90° relative to the magnetic field at 20 K and 25 μW microwave power with 2.5 G modulation amplitude. , Spectra of the respective Mn 4 O 5 Ca cluster signals were recorded for each sample at 8 K with 30 mW microwave power and 32 G modulation amplitude. The various MLS spectra were background-corrected by light-minus-dark subtraction (i.e., the difference between the spectra after and before sample illumination).…”
Section: Methodsmentioning
confidence: 99%